Penerapan Standar Pengelolaan Surat dalam Meningkatkan Efektivitas Manajemen Persuratan - Tengku Darmansyah; Amelia Amelia; Ibnu Qital Pasaribu; Irma Tussa’diyah Hasibuan; Wardah Sahrani Sibarani (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The research in this journal article aims to determine the application of letter management standards in increasing the effectiveness of letter management. Therefore, it is necessary to manage letters well and correctly so that the letters can be well organized and the process of returning letters can be carried out effectively and efficiently. It is hoped that effective mail management can be carried out by the relevant staff in managing mail, both for incoming and outgoing mail. So, in researching this journal article, it can be seen that the application of letter management standards in increasing management effectiveness, that the management of incoming mail is divided into six stages which are important to know, namely: receiving letters, sorting letters, directing letters, recording letters, distributing letters and storing letters. Meanwhile, for managing outgoing letters, there are also six stages which include: creating a letter concept, typing, editing, affixing a letter address, folding and enclosing the letter and distributing the letter. The implementation of management has gone quite well, and currently the system is being transferred to an electronic system.